Voter coercion and pro-poor redistribution in rural Mexico - Dragan Filipovich; Miguel Ni\~no-Zarazúa; Alma S. Santillán Hernández (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Voter coercion is a recurrent threat to pro-poor redistribution in young democracies. In this study we focus on Mexico's paradigmatic Progresa-Oportunidades-Prospera (POP) programme. We investigate whether local mayors exploited POP to coerce voters, and if so, what effect these actions had on the municipal incumbent's vote. For identification of vote coercion, we exploit the fact that the so-called 'enlaces municipales'-a municipal liaison officer that under strict apolitical rules acted as the link between the municipal administration and POP-were discontinued in 2008, but then restored in 2010. Our empirical strategy relies on an innovative 'difference-in-differencesin-discontinuities' design, which allows us to compare how election results in competitive electoral districts before and after the discontinuation and restoration of enlaces differed between communities with and without POP. Overall, we find that in close elections, the discontinuation of enlaces increased the vote share to the incumbent by approximately 10.5 per cent, while their restoration decreased that vote share by 6.4 per cent. The results suggest that the discontinuation of enlaces created a rules-free environment that allowed local incumbents to coerce beneficiaries to achieve an electoral gain. A review of the existing ethnographic literature on the role of enlaces in POP's operations provides further evidence to support our findings. Our study underscores the importance of implementing clear and well-designed rules to prevent the political capture of social policies.
Keywords: H53; I38; N36; P16; 330; voter coercion; clientelism; conditional cash transfers; rural poverty; Mexico